Thai EFL university students views on the effectiveness of Duolingo for enhancing listening and speaking skills - Yueh Yea Lo; Shanina Sharatol Ahmad Shah; Zuwati Hasim; Fatiha Senom; Mohd Rashid Mohd Saad; Pateera Thienpermpool (Studies in English Language and Education, 2025)
The current study aims to assess 150 Thai English as a Foreign Language (EFL) first-year university students perspectives on the efficacies of Duolingo, a popular mobile language application in improving English listening and speaking skills. Given the growing importance of mobile-assisted language learning (MALL) in enhancing language proficiency, this study investigates Duolingos potential to address the common challenges faced by EFL learners in developing these essential skills. The data were collected using a quantitative method, namely a structured questionnaire, to record participants attitudes towards Duolingo and corresponding experiences. Simultaneously, Gibson and Browns (2009) thematic technique was employed to analyse the open-ended responses. The results show that a high Duolingo usage level was discovered at 32.0% daily usage and 42.0% several times weekly, which underscored Duolingo integration into linguistic learning journeys. The participants also pinpointed crucial benefits, such as affordability, structured learning, convenience, diverse content, interactivity, audio exercises, and adaptive technologies. Nevertheless, 26.0% of the students described several limitations, including audio quality discrepancies, insufficient real-life conversational practices, and limited topic coverage. Furthermore, a significant gender distribution was demonstrated, with 70.7% females and 29.3% males. The findings posit that female students tended to or possessed higher accessibility to language learning technologies, including Duolingo. The findings reflect broader societal factors impacting educational preferences and opportunities. The study outcomes also contributed to educators and developers to improve digital tools for diverse language learning requirements.